Estudo da Arquitetura Bronco-vascular e determinação da segmentação pulmonar em cães. LMONAR EM CÃES - Mariana Zanini Maia (2023)
The anatomical-surgical segmentation and the study of the vascular architecture from an ex-vivo model allows the detailing of several systems and organs in domestic and wild species, in a complementary way to the traditional morphological anatomy. This study was conducted with the aim of understanding and describing the broncho-vascular architecture and pulmonary segmentation of dogs. For this purpose, 44 pairs of canine lungs originating from euthanized individuals in a zoonosis control center rotine were used. After the chest radiography and necropsy to separate the pairs of lungs, the technique of injecting a low-transfer colored acrylic resin into arteries, veins and pulmonary bronchi was used, followed by corrosion in a 7.5% sodium hydroxide solution. After the complete corrosion process, solid negative models of the beds of interest were obtained, enabling the evaluation of the structures that make up the functional sublobar units, also known as lungs segments. Furthermore, it was possible to describe the specificities of the course and pulmonary characteristics of the canine bronchial and vascular tree as a tool for enhancing future surgical approaches to the organ. It was concluded that the injection and corrosion model used in this study constituted a valuable tool for determining the details of canine pulmonary architecture, obtaining characteristics of the organ's segmental bronchovascular distribution, which is still incipient in the literature. At least 10 segments were identified in the right lung and 7 in the left lung in dogs, different from what is currently proposed by the Veterinary Nomina Anatomica. Additionally, the architecture and bronchovascular relationship of the entire organ were highlighted, especially the delineation of caudal lobes from intersegmental veins, which are crucial for defining pulmonary segments in humans. Keywords: lung; anatomy; lung segment; corrosion cast.